1989
DOI: 10.1111/j.1744-7348.1989.tb02102.x
|View full text |Cite
|
Sign up to set email alerts
|

Stem canker (Rhizoctonia solani) on five early and seven maincrop potato cultivars I. Infection of shoots, stolons and tubers

Abstract: In 1983 and 1984, potato seed tubers of five early and seven maincrop cultivars were inoculated with cultures of Rhizoctonia soluni during planting to simulate severe seed infection. Shoot and stolon infection was assessed in June-August and black scurf on tubers recorded after harvest in October.Almost all shoots of all cultivars had stem canker in both years and disease on shoots, stolons and tubers was more severe in 1984 than in 1983. In 1983 similar amounts of disease developed on all early cultivars and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 7 publications
1
12
0
Order By: Relevance
“…Sprout girdling may result in delayed emergence and delayed tuber bulking (Banville 1989, Carling et al 1989Hide et al 1989). As stolons are pruned and tuber set is reduced, there are fewer tubers per plant to act as sinks for products of photosynthesis.…”
mentioning
confidence: 99%
“…Sprout girdling may result in delayed emergence and delayed tuber bulking (Banville 1989, Carling et al 1989Hide et al 1989). As stolons are pruned and tuber set is reduced, there are fewer tubers per plant to act as sinks for products of photosynthesis.…”
mentioning
confidence: 99%
“…Whilst R. solani is well known to delay emergence (Secor and Gudmestad, 1999) the combined presence of these organisms may further extend the period taken for plants to emerge as indicated by Figure 1. A further delay in emergence may be critical since previous research has shown that stem canker symptoms increase very little (Hide et al, 1989) or even decrease (Simons and Gilligan, 1997) after plant emergence. Van Emden (1965) hypothesised that potato stems gained resistance to stem canker following exposure to light, which causes a switch to autotrophic nutrition.…”
Section: Discussionmentioning
confidence: 98%
“…When severe, such lesions may girdle the entire circumference, ultimately leading to the pruning of infected stems and stolons. Both stem and stolon canker, therefore, are of economic significance since they can result in malformation of developing daughter tubers (Scholte, 1987), a reduction in yield in some early cultivars (Hide et al, 1989) and uneven emergence that gives rise to non-target size tubers (Hide et al, 1973). Whilst the development of black sclerotia on the skins (black scurf) of harvested tubers has no effect on tuber yield, it can significantly downgrade the marketable value of seed tubers (Jeger et al, 1996) and reduce the saleability of ware to prepack markets.…”
Section: Introductionmentioning
confidence: 99%
“…Treating seed pieces with a chemical protectant prior to planting has been reported to be effective in the management of stem cankers and black scurf (Hide & Cayley 1982;Hide & Read 1985;Harris et al 1986). In recent years, increases in the incidence and severity of black scurf have been observed (Hide & Read 1985;Hide et al 1989;Folsom et al 1995). However, few studies have addressed the factors important for such an increase.…”
mentioning
confidence: 92%